Bistable and integrated based tuple model of risk characteristics - Корченко, Александр Григорьевич; Казмирчук, Светлана Владимировна; Дрейс, Юрий Александрович; Гололобов, Андрей Юрьевич (Ukrainian Information Security Research Journal, 2016)
Often experts of corresponding companies in order to increase the efficiency of information security decision making, put the question on the choice of existing or development of new means of security risks assessment of information systems resources. For the effective organization of appropriate process of a choice or development it is necessary to have a complete display of risk characteristics. In this regard, the most of the basic characteristics of risk for the information security sphere are defined in the work. According to this, it is proposed to display the characteristics of identification and assessment as a bistable integrated model of a tuple. In practice such model is offered to be used as a display on two particular tuples – analytical and synthetic, applied according to the choice implementation of existing means and to assist developers at creation of new risk assessment systems